When the people rule : popular sovereignty in theory and practice - Atanassow, Ewa; Bateman, David A. (David Alexander); Bartscherer, Thomas (SSRC anxieties of democracy., 2023)
In recent decades, popular sovereignty has come under increasing pressure. The rise of populism, often illiberal or authoritarian, has undermined minority rights, individual autonomy, and rule of law. The expansion of international institutions and greater reliance on market and non-governmental organizations have gradually insulated large areas of policymaking from public control. In turn, these developments cast doubt on the viability and desirability of liberal democracy itself. When the People Rule argues that comprehending and responding to the political crises of our time requires a radical refocusing on popular sovereignty. Each chapter offers a fresh perspective and opens new avenues of inquiry into popular sovereignty, advancing debate over the very heart of this principle - what it means for the people to rule. Thorough and timely, this volume is also available as Open Access on Cambridge Core.